Molecular Characterization of a cDNA Encoding of an Anionic Cysteine-Free Antimicrobial Peptide From the Iranian Scorpion Odontobuthus Doriae Venom Glands - Amir Jalali; Masoud Mahdavinia; Hamid Galehdari; Masoumeh Baradaran; Davood Valdi-Biranvand; Maryam Naderi Soorki (Mazandaran University of Medical Sciences, 2022)
Background: The venom peptides from the scorpion fauna of Iran have been poorly characterized so far. Objectives: In this study, we identified a cDNA encoding of an anionic cysteine-free antimicrobial peptide from the Iranian yellow scorpion odontobuthus doriae (O.doriae). Methods: The cDNA sequence of an anionic antimicrobial-peptide (AMP) was determined from the venom gland cDNA library of Iranian yellow scorpion O.doriae and was named ODAMP5. This sequence was characterized by a software. Then, the structure and function of its putative peptide were predicted in a bioinformatics manner. The library was constructed from 6 scorpion venom glands. The cDNA related to ODAMP5 was isolated from one positive clone of the library. Results: The analysis of ODAMP5 reveals a 51-residue mature peptide with an anionic property that was stable in physiological states. ODAMP5 was similar to anionic peptide Aba-2 from Androctonus bicolor and according to its structure, it can be a member of helical structure AMPs with a new type of putative conserved domain. Putative ODAMP5 has a small size which makes it convenient for synthesis. Conclusion: Furthermore, we created a framework to express the ODAMP5 peptide for future biomedical and pharmacological studies. ODAMP5 may be a new suitable therapeutic strategy for bacterial infection among a few recognized scorpion venom peptides without disulfide bridges.